CXCL12 and CXCR4, but not CXCR7, are primarily expressed by the stroma in head and neck squamous cell carcinoma. Issue 1 (January 2015) - Clatot, Florian; Cornic, Marie; Berghian, Anca; Marchand, Vinciane; Choussy, Olivier; El Ouakif, Faissal; François, Arnaud; Ruminy, Philippe; Laberge-Le-Couteulx, Sophie; Picquenot, Jean-Michel; Jardin, Fabrice
Abstract : Summary: The CXCL12/CXCR4 axis is involved in numerous models of metastatic dissemination, including head and neck squamous cell carcinoma (HNSCC). We assessed the relative expressions of CXCL12, CXCR4 and CXCR7 in the stroma and the tumour of HNSCC, and evaluated the methylation status of the CXCL12 promoter. Snap-frozen, HPV negative HNSCC samples were micro-dissected to isolate the tumoural and stromal compartments. The expression levels of CXCL12, CXCR4 and CXCR7 were assessed by qRT-PCR, and the methylation level of the CXCL12 promoter was evaluated by pyrosequencing. In total, 23 matched tumour/stroma samples were analysed. Higher expressions of CXCR4 and CXCL12 were observed in the stroma ( p = 0.012 and p < 0.0001, respectively). No significant difference in expression was observed for CXCR7. A high methylation level (>40%) of the CXCL12 promoter was observed in only a few tumoural samples (5/23) and was associated with a lower expression of the gene ( p = 0.03). Stromal cells, rather than the tumour itself, are mainly responsible for the expression of both CXCL12 and CXCR4 expression in HNSCC. CXCR7 expression did not differ between the two compartments and was not related to CXCL12 or CXCR4 expression. Finally, the methylation of the CXCL12 promoter could only explain the low intra-tumoural expression of this gene in 20% of cases. Abstract : Supplemental Digital Content is available in the text